2020
DOI: 10.3389/fped.2020.00442
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adjunctive Therapy in Acute Kawasaki Disease in Latin America

Abstract: Results: Of these patients, 1,152 received only a single dose of IVIG, and 266 received additional treatment. Age at onset was similar in both groups (median 2 vs. 2.2 years, respectively). The majority of patients were male (58 vs. 63.9%) and were hospitalized with the first 10 days of fever (85.1 vs. 84.2%). The most common adjunctive therapy administered was steroids for IVIG-resistance, followed by additional doses of IVIG. The use of biologics such as infliximab was limited. KD patients who received adjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…IVIG is the first-line treatment for KD [ 32 , 33 ]. However, clinicians are recommended to consider adjunctive treatment [ 34 , 35 , 36 ] like corticosteroids, infliximab, etanercept, plasmapheresis, and secondary IVIG infusion [ 1 ], especially in cases in which there is an increased risk of developing CAA. Further research is needed to clarify the role of adjuvant therapy in patients with concomitant KD and rotavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG is the first-line treatment for KD [ 32 , 33 ]. However, clinicians are recommended to consider adjunctive treatment [ 34 , 35 , 36 ] like corticosteroids, infliximab, etanercept, plasmapheresis, and secondary IVIG infusion [ 1 ], especially in cases in which there is an increased risk of developing CAA. Further research is needed to clarify the role of adjuvant therapy in patients with concomitant KD and rotavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peripheral platelet counts in the former KD patients were higher than those in the latter patients although not to a statistically significant extent. Higher levels of serum CRP and lower platelet counts were risk factors for predicting resistance to IVIG therapy in KD patients ( 15 , 26 , 27 ). From the aspect of laboratory findings, it was also indicated that patients who developed KD during the summers of years with large HFMD epidemics showed good responsiveness to IVIG.…”
Section: Discussionmentioning
confidence: 99%